APLIKASI I-CIBI: RESPON POSITIF DARI GURU, ORANGTUA DAN ANAK DENGAN KECERDASAN DAN BAKAT ISTIMEWA - Nurhastuti, Nurhastuti; Budi, Setia; Damri, Damri; Yuliana, Syari; Wulandari, Putri Lagenda; Nasri, Yosa Yulia; Mardhatillah, Mardhatillah; Handayani, Endang Sri (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
This study explores the positive response to the I-CIBI application, an innovative solution to support learning for gifted and talented children in Indonesia. Using a mixed-method approach with a sequential explanatory design, this research involved 29 respondents, consisting of teachers and parents. The results show that the I-CIBI application successfully meets specific needs in gifted education, with features including comprehensive testing and evaluation, personalized learning, and social-emotional skills development. Evidence-based pedagogical approaches and adaptive technology integration promote student motivation and active engagement. Despite implementation challenges, such as technology accessibility and integration with the national curriculum, the I-CIBI application demonstrates significant potential in optimizing the development of gifted and talented children. This research highlights the importance of collaboration among education stakeholders and continuous evaluation to ensure the long-term effectiveness of the application in the Indonesian educational context.